2019
DOI: 10.31234/osf.io/568wp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sweet nothings: No effect of self-control exertion on blood glucose levels

Abstract: Prior research has suggested that circulating levels of glucose in the bloodstream help to determine success at self-control. However, this idea has been challenged on multiple grounds. The current research added new evidence to the debate by testing 1) the extent to which exercising self-control reduces blood glucose levels, 2) whether consuming glucose, rinsing the mouth with glucose, or consuming aspartame (a sugar substitute) increases blood glucose levels, and 3) the extent to which measured blood glucose… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…On one side, the bug view proposes that the cost reflects biophysical constraints. For example, selfcontrol could consume a limited glucose supply, although this hypothesis has been vigorously disputed [40]. The exercise of control could also temporarily deplete neurotransmitter levels, such as dopamine [36], and/or contribute to the buildup in the brain of toxic waste products like amyloidbeta [38].…”
Section: Evaluation Of a Control-related Costmentioning
confidence: 99%
“…On one side, the bug view proposes that the cost reflects biophysical constraints. For example, selfcontrol could consume a limited glucose supply, although this hypothesis has been vigorously disputed [40]. The exercise of control could also temporarily deplete neurotransmitter levels, such as dopamine [36], and/or contribute to the buildup in the brain of toxic waste products like amyloidbeta [38].…”
Section: Evaluation Of a Control-related Costmentioning
confidence: 99%
“…Although indicators like heart rate variability, blood pressure and respiratory rate were studied in the context of mental fatigue (Richter et al, 2008 ; Hsu et al, 2015 ), it seems to be based on mechanisms that are rather separate from those that physical fatigue is usually characterized by, which originate in skeletal muscle activity (Dantzer et al, 2014 ; Abd-Elfattah et al, 2015 ). Moreover, the effects for theta and alpha band activity may not be as significant as shown in some previous studies, which corroborates the notion, as well as previous evidence, that pinpointing a physiological marker of mental fatigue is difficult (Dantzer et al, 2014 ; Abd-Elfattah et al, 2015 ; Brietzke et al, 2021 ) (also see the discussion on the role of glucose in effortful self-control as well as related research in the psychology of sports and performance: Carter et al, 2004 ; Chambers et al, 2009 ; Beedie and Lane, 2012 ; Molden et al, 2012 ; Sanders et al, 2012 ; Carter and McCullough, 2013 ; Hagger and Chatzisarantis, 2013 ; Finley et al, 2019 ). Due to this, subjective declarations of increased fatigue and tiredness as well as decreases in performance effectiveness are the main indicators of mental fatigue in previous research.…”
Section: Self-regulation Self-control and Effortmentioning
confidence: 99%
“…Initial evidence suggested that glucose could be the depleted resource specified by the strength model as responsible for self-regulatory failures (e.g., . However, reanalysis of the original data (Kurzban, 2010) and accumulating evidence (e.g., Finley et al, 2019;Baumeister & Vohs, 2016a) strongly contradicts this idea. 13 Interestingly, strong support still exists that ingesting (Masicampo & Baumeister, 2008;McMahon & Scheel, 2010;Wang & Dvorak, 2010) or swishing glucose in the mouth (Carter & McCullough, 2013;Hagger & Chatzisarantis, 2013;Molden et al, 2012;Sanders et al, 2012) mitigates the depletion effect.…”
Section: Glucosementioning
confidence: 99%